Sucrose synthase determines carbon allocation in developing wood and alters carbon flow at the whole tree level in aspen. Issue 1 (3rd July 2020) - Dominguez, Pia Guadalupe; Donev, Evgeniy; Derba‐Maceluch, Marta; Bünder, Anne; Hedenström, Mattias; Tomášková, Ivana; Mellerowicz, Ewa J.; Niittylä, Totte
Summary: Despite the ecological and industrial importance of biomass accumulation in wood, the control of carbon (C) allocation to this tissue and to other tree tissues remain poorly understood. We studied sucrose synthase (SUS) to clarify its role in biomass formation and C metabolism at the whole tree level in hybrid aspen ( Populus tremula  ×  tremuloides ). To this end, we analysed source leaves, phloem, developing wood, and roots of SUSRNAi trees using a combination of metabolite profiling, 13 CO2 pulse labelling experiments, and long‐term field experiments. The glasshouse grown SUSRNAi trees exhibited a mild stem phenotype together with a reduction in wood total C. The 13 CO2 pulse labelling experiments showed an alteration in the C flow in all the analysed tissues, indicating that SUS affects C metabolism at the whole tree level. This was confirmed when the SUSRNAi trees were grown in the field over a 5‐yr period; their stem height, diameter and biomass were substantially reduced. These results establish that SUS influences C allocation to developing wood, and that it affects C metabolism at the whole tree level. Abstract : See also the Commentary on this article by Gessler, 229 : 8–10 .